A study of synthetic aperture radar imaging with compressed sensing - Wen, Bihan. (2012)
Synthetic Aperture Radar (SAR) is a popular and important high resolution radar imaging method. Compressed sensing is an emerging technology with potential to reduce high data acquisition, storage, and transmission of conventional SAR. In this paper, we present a SAR imaging study with compressed sensing (CS). In this study, random aperiodic array is used for SAR imaging and the split bregman method is used for compressed sensing (CS) recovery. Both computer simulation and experiment results show that the proposed CS approach is effective in SAR target detection.